The answer is –x + 5 = 6x - 2. This is because of the Transitive Property.
You most likely remember the transitive property as "if a = b and b = c, then a = c." In this case, if y = -x + 5 and y = 6x - 2, then -x + 5 = 6x - 2.
Answer:
Step-by-step explanation:
28 BECAUSE IT CONTINUES THE PATTERN OF SUBTRACTING 4 FROMTHE AMOUNT PULLED PER GRADE
Answer:
£13800
Step-by-step explanation:
1150*12=£13800
Answer:
(0,0)
Step-by-step explanation:
x value of vertex = -b/2a
ax^2+bx+c
-2x^2+0x+0 sinc you have no value of b & c in your quadratic function
-b = 0
2a = (2)(-2)
-b/2a = (0/-4) = 0
x value of the vertex = 0
plug 0 in for all values of x in the function to find y coordinate value
-2(0)^2 = 0
(x,y) = (0,0)